Hypodontia and Hyperdontia among Libyan Orthodontic Patients - Mohammad , Fathia; Ingafou, Mohammed (Libyan Journal of Dentistry, 2021)
Background: it is not uncommon for orthodontist to come across patients with dental anomalies such as disturbances in teeth number. Hypodontia is a developmental absence of one or more teeth excluding the third molars, while hyperdontia (supernumerary teeth) is the presence of ‎additional tooth in the normal series. Objectives: The purpose of this study was to investigate the prevalence of hypodontia and hyperdontia in Libyan patients with different types of malocclusion. Material and Method: This is retrospective review of the pretreatment dental casts of consecutive patients attending at the department of Orthodontics in the University of Benghazi as well as their panoramic radiographs (OPGs) to look at the disturbances in the tooth number in the study group which was comprised 516 Libyan patients with an age range of 10 years to 34 years at the time of investigation. Results: A total of eighteen patients had either hypodontia or hyperdontia. The former was detected in 10 (1.76%) cases, 5 (0.88%) lateral incisors, 3 (0.53%) premolars‎ and 2 (0.35%) third molars, while hyperdontia was detected in another 8 cases, 4 (0.70%) mesiodenses, ‎2 (‎0.35%) premolar and 2 (0.35%) of 3rd molar. Conclusion: The number of patients with hypodontia and hyperdontia in this sample was apparently different from ‎those previously reported worldwide figures. However, further large scale studies are required to ascertain their ‎true prevalence and impact on Libyan population.‎